Effects of translational and rotational degrees of freedom on the properties of model water - Mohorič, T.; Hribar-Lee, B.; Vlachy, V. (Condensed Matter Physics, 2015)
Molecular dynamics simulations with separate thermostats for rotational and translational motions were used to study the effects of these degrees of freedom on the structure of water at a fixed density. To describe water molecules, we used the SPC/E model. The results indicate that an increase of the rotational temperature, TR, causes a significant breaking of the hydrogen bonds. This is not the case, at least not to such an extent, when the translational temperature, TT, is raised. The probability of finding an empty spherical cavity (no water molecule present) of a given size, strongly decreases with an increase of TR, but this only marginally affects the free energy of the hydrophobe insertion. The excess internal energy increases proportionally with an increase of TR, while an increase of TT yields a much smaller effect at high temperatures. The diffusion coefficient of water exhibits a non-monotonous behaviour with an increase of the rotational temperature. Для вивчення впливу трансляцiйних та обертових ступенiв вiльностi на структуру води з фiксованою густиною використано метод молекулярної динамiки з двома окремими термостатами для обертових та
трансляцiйних рухiв. Для опису молекул води було використано модель SPC/E. Результати показують, що
збiльшення обертової температури, TR, призводить до значного розриву водневих зв’язкiв. Цiлком зворотнiм є випадок, принаймнi не до такої мiри, коли збiльшується трансляцiйна температура, TT. Ймовiрнiсть знайти сферичну порожнину (вiдсутня молекула води) заданого розмiру значно зменшується при
збiльшеннi TR, але це має лише незначний вплив на вiльну енергiю гiдрофобної вставки. Надлишкова
внутрiшня енергiя збiльшується пропорцiйно до збiльшення TR, в той час, як TT дає значно менший
ефект при високих температурах. Коефiцiєнт дифузiї води має немонотонну поведiнку при збiльшеннi
обертової температури.